ANALISIS TINGKAT KESEHATAN KEUANGAN PERUSAHAAN DENGAN METODE ALTMAN Z-SCORE - Triska Dewi Pramitasari; Ratnaning Tyasasih (Relawan Jurnal Indonesia, 2019)
The company's health level is needed to see if the financial condition of a company it is healthy or not. Based on the results of these measurements owners and parties of interest that are within the company can take over the company's decisions.This study aims to assess and determine the use of Z-score method to analyze the financial soundness of the company. The sample in this study is cosmetic and household listed on the Stock Exchange as many as five companies during the period 2013 to 2017, where analyzed using discriminant analysis Altman Z-score (model Original Z-score).The results showed that of the five cosmetics companies and utilities are listed on the Stock Exchange, there are three companies that have a level of financial health is not stable (always changes every year), namely PT. Akasha Wira International Tbk., PT. Martina Berto Tbk.and PT. Mandom Indonesia Tbk. Meanwhile, two other companies have a level of financial health has been stable,PT. Mustika Ratu Tbk. and PT. Unilever Indonesia Tbk